1998
DOI: 10.1159/000030035
|View full text |Cite
|
Sign up to set email alerts
|

Tumour Markers and Their Prognostic Value in Adenocarcinoma of the Cervix

Abstract: Ninety-one patients with adenocarcinoma of the cervix had 4 tumour markers (TMs) assayed before treatment. Serum squamous cell carcinoma antigen (SCC) (n = 91) was raised in 25%; tissue polypeptide antigen (TPA) (n = 78) was raised in 35%; carcinoembryonic antigen (CEA) (n = 34) was raised in 26% and CA 125 (n = 64) was raised in 27% of these patients. In 47 of these 91 patients (52%), 1 or more of the markers were raised. The percentage of patients with raised TM increased with advancing stage. Univariate sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…Elevated CA 125 levels are detectable in 20-75% of patients with cervical adenocarcinoma [12,19,23,24,76,[85][86][87][88][89] (Table 5), and are associated with advanced tumour stage [86,87], large tumour size [28,87], high histological grade [87,88], lymph-vascular space involvement [90], deep cervical stromal invasion [28,90] and lymph node involvement [28,87,90]. In a series including 163 patients with stage Ib-IIa cervical adenocarcinoma treated with radical hysterectomy, the median pre-operative CA 125 value was 34.0 U/ml for patients with positive nodes compared with 17.6 U/ml for those with negative nodes (p = 0.0012) [90].…”
Section: Incidence Of Elevated Pre-treatment Serum Ca125 Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated CA 125 levels are detectable in 20-75% of patients with cervical adenocarcinoma [12,19,23,24,76,[85][86][87][88][89] (Table 5), and are associated with advanced tumour stage [86,87], large tumour size [28,87], high histological grade [87,88], lymph-vascular space involvement [90], deep cervical stromal invasion [28,90] and lymph node involvement [28,87,90]. In a series including 163 patients with stage Ib-IIa cervical adenocarcinoma treated with radical hysterectomy, the median pre-operative CA 125 value was 34.0 U/ml for patients with positive nodes compared with 17.6 U/ml for those with negative nodes (p = 0.0012) [90].…”
Section: Incidence Of Elevated Pre-treatment Serum Ca125 Levelsmentioning
confidence: 99%
“…Among these latter, the logistic regression showed that pre-operative serum CA 125 > 26 U/ml was related to lymph-vascular space invasion (p = 0.04) and deep cervical stromal invasion (p = 0.002). Patients with cervical adenocarcinoma sometimes showed raised levels of 28,89,91] and CEA [33,85,86,88,89,91,92], first identified in tissue and serum samples from patients with colon cancer.…”
Section: Incidence Of Elevated Pre-treatment Serum Ca125 Levelsmentioning
confidence: 99%
“…It has been reported that serum CA 125 levels are elevated in 20-75% of untreated patients with cervical adenocarcinoma [5,10,12,13,16], while serum CEA is elevated in 19-50% [4,4,12,13,16], serum SCC in16-57% [4,5,9,10,13], and CA 19-9 in 42% [16]. Some of these studies have also indicated that serum tumor marker levels in patients with cervical adenocarcinoma are correlated with the clinical course [5,12,13,15,16]. With respect to recurrent disease, the positive rate of serum CA 125 was reported to be 43-71%, while serum CEA was positive in 14-36%, and serum SCC in 23-29% [4,12,13,15].…”
Section: Discussionmentioning
confidence: 99%
“…Some of these studies have also indicated that serum tumor marker levels in patients with cervical adenocarcinoma are correlated with the clinical course [5,12,13,15,16]. With respect to recurrent disease, the positive rate of serum CA 125 was reported to be 43-71%, while serum CEA was positive in 14-36%, and serum SCC in 23-29% [4,12,13,15]. However, the number of recurrent cases in these studies was very limited, and little attention was paid to the difference between adenocarcinoma and adenosquamous carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation